DAMPAK PENGGUNAAN EKONOMI DIGITAL TERHADAP TINGKAT PENDAPATAN PADA UMKM CIRENG TUBAN ALA MBAK MIRA - Arti Mirza Aulia; Shalsa Billa Eka Putri; Farah Arda Wardani; Maria Yovita R. Pandin (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
The digital economy has become a key pillar in the development of Micro, Small and Medium Enterprises (MSMEs) in the modern era. Digital transformation, through the application of technology in business operations, opens up new opportunities to increase revenue and expand markets. MSMEs, as the backbone of the Indonesian economy, have the potential to thrive with digital technology. This study evaluates the impact of the digital economy on the revenue of Cireng Tuban Ala Mbak Mira MSMEs, which utilize digital technology to optimize revenue. Qualitative methods were used by collecting primary data through interviews. The results showed a significant increase in revenue after the adoption of online food delivery apps such as GoFood, ShopeeFood, and GrabFood, with revenue increasing steadily every year, highlighting the benefits of digitalization in expanding markets and operational efficiency.